Cluster-Based Analysis on State Industrialisation Development:Strenghts, Challenges and the Strategic Action Agenda for the State Government of Perak - Mohd Nurzid, Mohd Nur Azlan (2003)
This study presents the findings on the current status and performance of the Perak State Industrialisation drive. Industrial Cluster Analysis by way of applying the Porter’s Diamond Model to determine the suitability of a particular industry to the nation or region’s competitive advantage has been gaining popularity since its introduction in the 1990’s. The Second Malaysia Industrial Masterplan 1996-2005 (IMP2) has embraced this Cluster-Based Industrial Development framework by promoting the “manufacturing plus plus” concept. Due to difference of development pace among States in Malaysia, an attempt was made to apply the Porter’s Diamond Model to determine the competitiveness advantage of eight State promoted industry group in Perak: Electrical and Electronic (E&E), Machinery and Engineering Services, Metal Fabrication, Rubber-Based Products, Wood-Based Products, Non-Metallic Minerals, Textile and Apparel and Food Products Industry. The research findings reveals that, except for the E&E industry group which Perak is a non-localised member of Penang and Selangor’s E&E industrial cluster, there is neither dept in the vertical value-chain nor in the related and supporting industries for the other industry studied. Local competitive demand akin to international standards are also missing in the State. Therefore the State of Perak diverse industrial base dictates an industrial development strategies in the more traditional program areas of recruitment, small business development, retention and expansion. The difficulties and high costs associated with developing new industry clusters may render clustering an impractical employment generation strategy.